2016
DOI: 10.1038/mt.2016.134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antitumor Immune Responses by Optimized Combinations of Cell-penetrating Peptide-based Vaccines and Adjuvants

Abstract: Cell penetrating peptides (CPPs) from the protein ZEBRA are promising candidates to exploit in therapeutic cancer vaccines, since they can transport antigenic cargos into dendritic cells and induce tumor-specific T cells. Employing CPPs for a given cancer indication will require engineering to include relevant tumor-associated epitopes, administration with an appropriate adjuvant, and testing for antitumor immunity. We assessed the importance of structural characteristics, efficiency of in vitro transduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…2). This was directly demonstrated using Zebra-derived CPPs, TAT, and penetratin [16, 22, 24, 46, 54, 55]. …”
Section: Multi-epitopic Antigenic Cargosmentioning
confidence: 99%
“…2). This was directly demonstrated using Zebra-derived CPPs, TAT, and penetratin [16, 22, 24, 46, 54, 55]. …”
Section: Multi-epitopic Antigenic Cargosmentioning
confidence: 99%
“…In addition, it was consistently shown, for various multiantigenic constructs, that CPP-mediated antigen uptake, not only with external adjuvant (10,11) but also within a self-adjuvanting protein, can promote CD8 and CD4 T cell immune responses. Furthermore, these immune responses were not limited to model antigens or neoantigens but were also induced for self-antigens both in mice (gp100 and gp70) and in NHPs (CEA, survivin, EPCAM, and MUC1).…”
Section: Discussionmentioning
confidence: 94%
“…We have previously demonstrated that this major drawback can be overcome by using cell-penetrating peptides (CPPs) as delivery vectors (10,11). These small peptides can cross the plasma membrane even when linked to large multiepitopic cargos, allowing antigens to be delivered into different processing compartments of DCs, so that they are presented on both MHC class I and class II, promoting CD8 and CD4 T cell activation, respectively (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the critical importance of adjuvant choice for therapeutic cancer vaccination revealed in preclinical studies (119121), this issue will eventually have to be addressed in a clinical context. Interestingly, subsequent to clinical and mice studies showing that preconditioning the tumor vaccine injection site by a recall response to tetanus/diphtheria improved lymph node homing of tumor antigen-bearing DCs and magnitude of immune responses (19), four studies (NCT02193347, NCT02709616, NCT02465268, NCT02366728) use a Td recall vaccine as adjuvant, some testing as part of their clinical trial efficiency of DC migration to lymph nodes (19).…”
Section: Ongoing Clinical Trials For Tumors In the Brainmentioning
confidence: 99%